Efficacy of extracorporeal shock wave treatment in calcaneal enthesophytosis. Issue 11 (1st November 2001) - Cosentino, R; Falsetti, P; Manca, S; De Stefano, R; Frati, E; Frediani, B; Baldi, F; Selvi, E; Marcolongo, R
Abstract : OBJECTIVE: To evaluate the efficacy of extracorporeal shock wave treatment (ESWT) in calcaneal enthesophytosis. METHODS: 60 patients (43 women, 17 men) were examined who had talalgia associated with heel spur. A single blind randomised study was performed in which 30 patients underwent a regular treatment (group 1) and 30 a simulated one (shocks of 0 mJ/mm 2 energy were applied) (group 2). Variations in symptoms were evaluated by visual analogue scale (VAS). Variations in the dimension of enthesophytosis were evaluated by x ray examination. Variations in the grade of enthesitis were evaluated by sonography. RESULTS: A significant decrease of VAS was seen in group 1. Examination by x ray showed morphological modifications (reduction of the larger diameter >1 mm) of the enthesophytosis in nine (30%) patients. Sonography did not show significant changes in the grade of enthesitis just after the end of the treatment, but a significant reduction was seen after one month. In the control group no significant decrease of VAS was seen. No modification was observed by x ray examination or sonography. CONCLUSION: ESWT is safe and improves the symptoms of most patients with a painful heel, it can also structurally modify enthesophytosis, and reduce inflammatory oedema.